Desa “Kutukan” Bagi Para Pejabat (Analisis Semiotika Mitos Joko Modo dari Rembang) - NFN Samidi (Jurnal Lektur Keagamaan, 2015)
This article is a summary of research on one of the myths that exist in Rembang, i.e. The Myth of Joko Modo. This myth is still believed by the society of Rembang. The myth of Joko Modo is the reason why officials or government employees do not dare to go to Hamlet Modo,Village Jadi,SubdistrictSumber Rembang. There is a myth that the officials will be wratched and get a disaster if they came to Hamlet Modo. The author used semiotic analysis of Ferdinand de Saussure to uncover the meaning of Joko Modomyth.The myth of Joko Modo is a form of public communication through signs and the specific code that has values of local wisdom. The semiotic meanings of Joko Modo mythsuch as: socio-cultural settings of emergence of myth is an agrarian society, social class differences and economic levels in a community can become a trigger of conflict, and the importance of self-identity or territory.